Abnormal physiological responses toward sensory stimulus are related to the attention deficits in children with sluggish cognitive tempo - Yung, Trevor W. K.; Lai, Cynthia Y. Y.; Chan, Chetwyn C. H. (Frontiers in Neuroscience, 2022)
Previous studies have found that sluggish cognitive tempo (SCT) is often associated with difficulties in real-life functioning, such as social problems, emotional difficulties, and academic learning difficulties. However, the underlying mechanisms contributing to the SCT symptoms and its associated real-life difficulties have still not been clearly understood. A previous study has found that SCT symptoms were associated with hypoarousal and hyperarousal toward the sensory stimulus. However, it is still unclear whether such abnormal arousal regulation is related to sustained attention difficulties that have been found to be related to social difficulties and withdrawn behavior in children with SCT. In this study, arousal regulation deficit in SCT is examined by the physiological responses quantified by HRV and EEG in the sensory challenge paradigm. This study aimed to establish a linkage between arousal regulation reflected by HRV and EEG and attention difficulties in children with SCT. The results of this study showed that higher theta power in the auditory stimulation condition than in the resting condition was associated with higher omission errors in sustained attention tasks in the SCT group. It was also found that higher parasympathetic activities during sensory stimulation conditions were associated with higher commission errors in the SCT group. These results reflected that hypersensitivity toward stressful sensitivity toward a stressful sensory stimulus is associated with attention difficulties in children with SCT. This further supported the notion that SCT should be conceptualized as a condition characterized by multiple deficits in different biological systems, such as the cognitive system, the negative valence system, and the arousal regulatory system.